Assessing 3D-modeling techniques based on a combination of positron emission tomography-and computed tomography as a means to detect tumor invasion of the paragastric tissue in gastric cancer: a pilot study - T. V. Khorobrykh; E. V. Poddubskaya; V. G. Agadzhanov; L. M. Tulina; I. V. Ivashov; A. V. Grachalov; M. A. Tsai; Ia. A. Drach; Z. A. Omarova (Сеченовский вестник)
Aim. To evaluate the diagnostic capabilities of combined positron emission tomography (PET) with accumulation of 18-fluorodeoxyglucose and computed tomography (CT) data, with additional 3D-visualization of CT DICOM files using the 3D Slicer software, in detecting tumor invasion of the paragastric tissue in locally advanced gastric cancer.Materials and methods. A prospective open-label study was conducted as part of the research project “SmartGastro”. Four women and four men aged 51 to 81 years with a histologically confirmed diagnosis of gastric cancer underwent combined PET/CT following the “Whole Body” protocol at 60–80 minutes after the administration of the radiopharmaceutical agent (RPA). The obtained results were analyzed through visual assessment of CT and PET images separately, as well as through fused scans, followed by 3D reconstruction based on CT DICOM data. All patients underwent surgery. The resected macroscopic specimen was stepwise excised along its perimeter, followed by a histological examination of the resection margins (paragastric fat tissue). In all cases, R0 resection was confirmed, indicating radical tumor removal. The initial delineation of tumor boundaries based on PET-CT and CT imaging was compared voxel-by-voxel with the secondary delineation performed through a visual assessment of the excised macroscopic specimen.Results. In 5 out of 8 cases, compromised peritumoral paracardial tissue detected on CT corresponded to regions of radiopharmaceutical agent uptake on PET. Areas demonstrating increased RPA accumulation in the peritumoral tissue, along with a corresponding rise in densitometric values on CT, were indicative of true invasion. This was confirmed by a histological examination of the resected specimen, in 6 out of 8 cases. The sensitivity of combined PET/CT, assessed on a voxel-by-voxel basis against postoperative pathological findings, was 0.88 (95% confidence interval (CI): 0.76–0.97), while specificity reached 0.91 (95% CI: 0.80–0.99). The discrepancy in tumor boundaries between these modalities, determined using the Hausdorff distance, was 5.2 mm, with a mean tumor size of 38×30×39 mm. Conclusion. Combined PET/CT enables the surgeon to identify precisely a compromised mesolayer adipose tissue.The construction of 3D-models of perigastric tissues affected by the tumor process, combined with the visualization of the gastric tumor and associated vasculature, facilitates comprehensive preoperative planning for oncological surgery.